SONA SUPER BASMATI: A NEW EXTRA-LONG GRAIN HIGH YIELDING RICE VARIETY WITH EXCELLENT COOKING QUALITY - SABAR, M; ALI, SS; IJAZ, M; KHAN, RAR; BIBI, T; RIAZ, M; SEHAR, H; SHAHZADI, F; ZAFAR, SA; JAVED, HM (Biological and Clinical Sciences Research Journal, 2024)
Abstract Rice crop feeds about half of the world’s population which is getting larger and hungrier with every tick of the clock. Basmati rice being a geographical speciality of Pakistan is widely proclaimed as one of the finest rice available throughout the world due to its unique aroma, taste, and texture. Changing consumer behavior and preferences for basmati rice i.e., extra-long grain length along with excellent cooking quality, reiterates the revitalization of rice breeding objectives to develop suitable basmati rice varieties. In this context, plant breeders at Rice Research Institute, Kala Shah Kaku identified a suitable transgressive segregant from F2 segregating population of a cross (PK 10436) between the famous basmati rice variety “Basmati 515” (female parent) and 99417 (male parent). The initial cross of PK 10436-4-2 was accomplished during Kharif, 2010 followed by its rigorous selection and purification in succeeding generations through the pedigree method till F4 generation in Kharif, 2014. After its development, PK 10436-4-2 was evaluated in Station Yield Trials (Kharif, 2016 - 2019) for various yields and its attributing traits in which it gave a cumulative 31.37 % yield advantage over the check variety (Super Basmati). Meanwhile, multi-locational yield evaluation was accomplished in Micro-plot Yield Trials and National Uniform Yield Trials for two consecutive years (Kharif, 2020 - 2021) at various locations across Pakistan; in which, PK 10436-4-2 out-yielded the check variety by 17.50 % and 19.75 % respectively. In addition to superior yield indices, PK 10436-4-2 showed excellent cooking quality i.e., extra-long grain length (AGL = 9.5 mm; CGL = 17.5 mm), with strong aroma. The aforementioned superior credentials of this candidate line led to its approval for general cultivation as “Sona Super Basmati” in the 56th meeting of the Punjab Seed Council, Punjab, Pakistan. In the future, prospects of cultivating Sona Super Basmati could create new vistas not only in local rice consumption but also in the basmati rice export of Pakistan.